Incorporation of carrot pomace powder in wheat flour: effect on flour, dough and cookie characteristics - Ahmad, Mukhtar (J Food Sci Technol, 2016)
Carrot pomace powder (CPP) of 72 and 120 mesh sizes was incorporated in wheat flour at 10, 15 and 20 % level and its impact on flour, dough and cookie characteristics was evaluated. Protein content of the flour blends (8.84–7.88 %) decreased and fibre content (4.63–6.68 %) increased upon blending of CPP in wheat flour. Wheat flour containing 120 mesh CPP showed better functional properties [water absorption (1.16–1.47 %), oil absorption (1.11–1.39 %), solubility index (41–50 %) and swelling power (1.34–1.39)] than those containing 72 mesh. Water solvent retention capacity and sucrose solvent retention capacity increased while lactic acid solvent retention capacity and sodium carbonate solvent retention capacity decreased with blending of CPP. Water absorption, dough development time and degree of softening increased whereas, dough stability and mixing tolerance decreased with increasing CPP. The highest decrease in pasting was observed flour containing 72 mesh CPP. Rheology of dough containing 120 mesh CPP closely resembled the control. Color of flour and cookies increased with blending of CPP irrespective of mesh size. Antioxidant activity of cookies was higher than the flour blends. The cookies containing CPP of 72 mesh showed the lowest hardness. However, cookies containing CPP of 120 mesh showed the best sensory properties. Incorporation of 120 mesh CPP produced low gluten cookies with manageable flour and dough characteristics and better antioxidant and sensory properties.